Postural Control and Functional Performance Changes with Inspiratory Muscle Training in Chronic Kidney Disease Patient - Rian Dewi Auriani; Vitriana; Farida Arisanti (Indonesian Journal of Physical Medicine & Rehabilitation, 2021)
ABSTRACTIntroduction: Approximately 60-75% of chronic kidney disease (CKD) patients have a uremicsyndrome that may cause damage to muscle cells, including the diaphragm as respiratory muscle, whichis known involved in maintaining postural stability and balance. This study aims to see the effects ofinspiratory muscle training on postural control and functional performance in CKD patients undergoinghemodialysis twice a week.Methods: This single-blind randomized controlled trial enrolled 36 participants (45±9 years) allocatedrandomly into the intervention and control group, receiving intensity of 50% and 10% MaximumInspiratory Pressure (MIP), respectively. Postural sway (95% ellipse area, anteroposterior (AP), andmediolateral (ML) sway) measured using a force platform in static standing with feet apart (FP1) andtogether (FP2), and functional performance by Short Physical Performance Battery (SPPB), assessed atpre-and postintervention.Results: After 8-week, intervention group demonstrated greater improvements on MIP (233.45% vs141.65%; p=0.0001). Postural sway FP1 and FP2 not significantly improved in intervention group (p >0.05). The control group showed a significant increase (p = 0.007) in the SPPB score.Conclusion: The inspiratory muscle training has not significantly improved postural control norfunctional performance in patients with chronic kidney disease on hemodialysis. Further research isneeded.Keywords: chronic kidney disease, hemodialysis, inspiratory muscle training, physical performance,postural control